Does access to credit matter in land transfer decision-making? Evidence from China - Yu, Xi; Su, Qin; Lyu, Jianxing (Frontiers in Environmental Science, 2023)
Land transfer is a favorable tool to solve the low land utilization rate caused by population aging and migration. Most previous studies on land transfer behavior focused on the participation and area of transfer, while little attention was paid to farmers’ future land transfer intentions. Hence, by building an analysis framework of land transfer-in “participation-area-future willingness,” this study uses the recent farm-level data from China to systematically examine the relationship between access to credit and land transfer-in decisions. To address the potential endogeneity and selection bias from the observable and unobservable factors, we employ the endogenous switching regression (ESR) model and endogenous switching probit (ESP) model for the analysis. The empirical results show that access to credit increases the expected probability of land transfer-in participation and futural intention, as well as helps to expand the land transfer-in area. Specifically, access to credit contributes to increasing the participation, area, and futural willingness of farmers’ land transfer-in by 62.6%, 126%, and 74.9%, respectively. The positive role of access to credit is confirmed by the estimates of the propensity score matching (PSM) approach. Our findings highlight that financial support through access to credit can encourage farmers’ land transfer-in decisions and further protect the limited arable land source.